A study on effect of conflit management to subordinate absenteeism at Majlis Pembandaran Batu Pahat : case study / Norazidah Hassan - Hassan, Norazidah (2015)
The purpose of writing is to investigate the relationship between supervisor's conflict and effective commitment towards absenteeism in Majlis Perbandaran Batu Pahat. This correlation research used stratified disproportionate sampling technique and the sample size using by Krejcie and Morgan (1970). The questionnaire were distribute to 80 respondent. The questionnaire were analyzed by using SPSS version 20 to determine the result. The result of reliability test has been done is 770 for the section B. It shows reliable and can use for the future. Meanwhile, reliability test for section Cis .767. It also show a reliable and can use for the future. The result of reliability test for the section Dis .677. So, it show reliable and also can be used for the future. The finding showed that there was a moderate relationship between conflict management and absenteeism is (r= .370**, n=80, p<.05, s=.001). At the same time, the finding also showed there was a moderate relationship between effective commitment and absenteeism is (r= .391 **, n=80, p<.05, s=000). On the other hand, the finding showed there have weak relationship between gender and working experience towards absenteeism. Relationship between gender and absenteeism is (r= .083, n=80, p>.05, s=.462). Relationship between working experience and absenteeism is (r= .037, n=80, p>0.05, s=.743). The recommendation in this research is to avoid the conflict management in Majlis Perbandaran Batu Pahat. Besides that, to increase their commitment and at the same to decrease their absenteeism.